2015
DOI: 10.1016/j.supflu.2014.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide loaded cellulose acetate mats as controlled topical O2 delivery devices

Abstract: a b s t r a c tIn this study, sub and supercritical CO 2 are used as effective solvents to impregnate hydrogen peroxide (H 2 O 2 ) into cellulose acetate (CA) non-woven mats. As much as 25 wt% H 2 O 2 can be impregnated at operating conditions of 25-45 • C and 1200 psig. Thermal gravimetric analysis shows that H 2 O 2 -loaded CA mats lose more than 60% of available H 2 O 2 when quickly heated to 37 • C and held at this temperature for 60 min. However, in comparison, pure H 2 O 2 -H 2 O (50:50 w/w) solution eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This phenomenon can be explained by participation of carvacrol with its hydroxyl group in intermolecular hydrogen bonds between CA chains leading to the change in solid structure of CA. Mallepally et al [7] showed that loading of up to 25% of hydrogen peroxide did not affect morphology of CA mats. Shen et al [8] also reported that loading of up to 10% of vanillin and L-menthol into CA fiber did not affect the morphology.…”
Section: Morphology Of Cellulose Acetate Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…This phenomenon can be explained by participation of carvacrol with its hydroxyl group in intermolecular hydrogen bonds between CA chains leading to the change in solid structure of CA. Mallepally et al [7] showed that loading of up to 25% of hydrogen peroxide did not affect morphology of CA mats. Shen et al [8] also reported that loading of up to 10% of vanillin and L-menthol into CA fiber did not affect the morphology.…”
Section: Morphology Of Cellulose Acetate Samplesmentioning
confidence: 99%
“…Amount of impregnated active substance and porous structure of the substrate (carrier) are of vital importance for controlled drug delivery and its efficiency against target bacterial strains. Amount of impregnated additive depends on complex interactions of ternary system (additivesupercritical fluid-polymer) which are affected by CO 2 pressure, temperature, nature of polymer, and time of its exposure to supercritical fluid [4,7,9]. Previous studies demonstrated that pure scCO 2 had negligible effect on CA morphology and thermal properties [5,8].…”
Section: Supercritical Impregnation Of Cellulose Acetate Withmentioning
confidence: 99%
See 3 more Smart Citations